Branding the City Through Mediterranean Identity: Local Cosmopolitan Ideologies and Narratives of Exclusion in Napoli, Marseille and Rijeka. - Cocco, Emilio; Sabatino, Pietro; Ragone, Marianna (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
The Mediterranean identity is becoming an intriguing tool for city authorities willing to implement policies of urban regeneration all over the basin. More specifically, all around the Mediterranean coast, independently on the national and local features, many cities are branding their identity as a “Mediterranean one” to promote gentrification projects, attract investments, develop tourism and re-shape their cultural identity for the global scene.In our paper, we are going to investigate the main common characters of this Mediterranean branding process by comparing three cases of very different Mediterranean cities: Napoli, Marseille and Rijeka. These cities are peripherally located within their national territories and although part of quite diverse nation-building process, they are all targets of regeneration policies that exploit their maritime immaterial and material heritage, usually emphasized by “big events” (such as ECOC in Marseille 2013 and Rijeka 2020, or the America’s cup in Napoli). Thus, our aim is twofold: on one hand we shall point out the common ideological features of this regeneration-oriented Mediterranean narrative by focusing on and deconstructing the driving concept of local cosmopolitanism. On the other one, we will explore the practices of exclusion hidden behind this Mediterranean narrative by stressing the unspoken discard and removal of some undesired people, histories and heritage from the picture of regeneration. Our investigation is based on the quantitative and qualitative analysis of tourist masterplans, city sponsored cultural promotion materials and audio-visual advertisements of the city. Also, visual ethnography of the urban beaches, port-areas and waterfronts aimed at detecting and quantifying landmarks, signs and symbols of the Mediterranean-ess.